"Normally I'd get really agitated, but I just laughed!": what do participants reflect upon in a transactional analysis/mindfulness based anger management programme?. Issue 4 (3rd July 2020) - Shepherd, Gary
ABSTRACT: Most anger management group programmes utilise Cognitive Behaviour Therapy (CBT) and Mindfulness Based Treatments (MBTs) in their interventions. This study uses Transactional Analysis (TA) and mindfulness to help promote behavioural change. We explored participants' phenomenological change throughout a 10-week anger management programme. The research examines participants' weekly "check-ins" as they reflected on their angry behaviours, their interpersonal relationships and the development of mindfulness techniques as a way to regulate their angry emotions. The research suggests participants engage in a group learning process of sharing their angry behaviours, reflecting upon the taught content of the programme before acting to change their behaviour, utilising the group for encouragement and support.